Incidence of postoperative hypocalcaemia in patients with preoperative cytological evidence of Hashimoto’s thyroiditis undergoing thyroidectomy - Joseph, Pauly T.; S., Sreekanth T.; Xavier, Alex (International Surgery Journal, 2021)
Background: Hashimoto’s thyroiditis is an autoimmune pathology presents as a painless goiterogenous condition. It manifests as hypothyroidism, occurring in females of the age group 30-40. Patients are operated for cosmetic symptoms or suspicions of malignancy. The surrounding adhesions and fibrosis of the gland makes it more prone for hypocalcaemia post operatively. This study was conducted to find the incidence of hypocalcaemia postoperatively in patients with Hashimoto’s thyroiditis. Methods: Patients above 13 years undergoing total thyroidectomy where completion thyroidectomy after hemi thyroidectomy, concurrent lymph node dissection, patients on calcium therapy or the ones with preexisting hypocalcaemia were excluded from the study. 100 patients were studied from 1 January 2018 to 1 January 2019 and corrected serum calcium levels at 24 hours, 48 hours and 2 weeks estimated postoperatively. Analysis was done using CSC sepi-info software. Qualitative data were analyzed with Chi square, Z test and ANOVA test. Results: Though 32/100 patients had hypocalcemic symptoms only 26 (26%) had low calcium biochemically. The association between Hashimoto’s thyroiditis and post thyroidectomy hypocalcaemia had significant association (p<0.0001). 11.53% (3/26) had recovered in 48 hours and at two weeks 10 patients remained hypocalcemic with a recovery of 61.53%. Conclusions: Hypocalcaemia after total thyroidectomy in Hashimoto’s thyroiditis occurs due to fibrosis in gland, adhesions to the adjacent structures, injury to the parathyroid glands during surgery and non-identification of parathyroid glands.